2014 22nd International Conference on Pattern Recognition 2014
DOI: 10.1109/icpr.2014.266
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Species Classification Based on a Botanical Shape Sub-classifier Strategy

Abstract: Within the framework of a smartphone-based application, helping people to identify plant species in the wild, a sub-classifier strategy has been introduced. It aims at recognizing the botanical properties of a leaf, relatively to various global and local shape criteria used in flora books. A decision function is applied on these classified shape categories to produce a final decision on the species of the leaf. In this paper, the fusion strategy and its corresponding Random-Forest-based sub-classifiers are des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The accuracy of the system without the fusion features was found to be 59.6% for fuzzy local binary pattern and 50.8% for fuzzy colour histogram, respectively. In another study, leaf species classification was conducted using a botanical shape sub-classifier strategy [43]. The implementation of fusion strategy and its corresponding random-forest-based sub-classifiers as part of a leaf recognition system.…”
Section: Probabilistic Neural Network (Pnn)mentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of the system without the fusion features was found to be 59.6% for fuzzy local binary pattern and 50.8% for fuzzy colour histogram, respectively. In another study, leaf species classification was conducted using a botanical shape sub-classifier strategy [43]. The implementation of fusion strategy and its corresponding random-forest-based sub-classifiers as part of a leaf recognition system.…”
Section: Probabilistic Neural Network (Pnn)mentioning
confidence: 99%
“…The fusion technique provides a significant accuracy enhancement compared to other proposed methods, while providing necessary information for educational purposes. [43]…”
mentioning
confidence: 99%
“…This approach, as mentioned earlier, relies on the user to select the base point and other reference points for segmenting and aligning the leaf. Another partial shape approach was proposed in [19], using a sub-classifier strategy based on the local and the global shape criteria in the flora books. Four sets of attributes have been considered to extract botanical labels input into a Random Forests classifier (RF) to identify the species of a plant.…”
Section: Related Workmentioning
confidence: 99%
“…Although there has been some work on flower classification [45] and large scale plant identification from learned categories [17], classifying leaves in order to determine the species is the most common approach. There is a large body of literature ( [40], [44], [25], [30], [8], [53], [11], [10], [43], [9], [34], [55], [61], [54], [28], [63]) over the last two decades on leaf recognition for plant species identification. Leaf classification was first reported by Mokhtarian et al [40].…”
Section: Related Workmentioning
confidence: 99%
“…The method achieves good performance on a public database of Swedish leaves, including leaves that are collected from 100 tree species. Some recent work ( [34], [54]) developed leaf recognition systems for mobile applications. Recently Zhao et al [61] demonstrated a computationally fast technique for leaf recognition.…”
Section: Related Workmentioning
confidence: 99%